Oxidative Addition of C–X Bonds and H–H Activation Using PNNP‐Iron Complexes. Issue 1 (2nd January 2020) - Gautam, Monika; Yatabe, Takafumi; Tanaka, Shinji; Satou, Naoto; Takeshita, Tomohiro; Yamaguchi, Kazuya; Nakajima, Yumiko
Abstract: Iron(0) complex bearing a phenanthroline‐based meridional PNNP ligand [Fe(PNNP)2 ( μ ‐N2 )] (1 ) (PNNP=2, 9‐bis((diphenylphosphino)methyl)‐1, 10‐phenanthroline) smoothly reacted with CH3 I at ambient temperature to cleave C–I bond, resulting in the formation of the corresponding oxidative addition product, [Fe(CH3 )(I)(PNNP)] (2 ). Complex 2 was fully identified by NMR and its structure was determined by a single crystal X‐ray diffraction study. Mechanistic study using cyclopropylmethyl bromide as a radical clock supported a radical pathway for the C–I bond cleavage of CH3 I. Complex 2 underwent deprotonation on treatment with NaO t Bu to form 4, which possessed a dearomatized phenanthroline backbone. Complex 4 further reacted with H2 to cleave H–H bond. The reaction was mediated by metal‐ligand cooperation process that involves re‐aromatization of the phenanthroline backbone of the PNNP ligand. Abstract : Iron(0) complex bearing a phenanthroline‐based meridional PNNP ligand [Fe(PNNP)2 ( μ ‐N2 )] (1 ) reacted with CH3 I to form the corresponding oxidative addition product, [Fe(CH3 )(I)(PNNP)] (2 ). On treatment of NaO t Bu, 2 underwent dearomatization of the phenanthroline backbone. The resulting complex further reacted with H2 to cleave H−H bond. The reaction was mediated by metal‐ligand cooperation process that involves rearomatization of the phenanthroline backbone of the PNNP ligand.